Leader-Following Multi-Agent Coordination Control Accompanied With Hierarchical Q(λ)-Learning for Pursuit - Zhu, Zhe-Yang; Liu, Cheng-Lin (Frontiers in Control Engineering, 2021)
In this paper, we investigate a pursuit problem with multi-pursuer and single evader in a two-dimensional grid space with obstacles. Different from the previous studies, this paper aims at addressing a pursuit problem in which only some pursuers can directly access the evader's position. In addition, a hierarchical Q($λ$)-learning with improved reward is proposed, and the simulation results show that the proposed method outperforms Q-learning.